India’s Top Company for Corporate Social Responsibility (CSR) - An Empirical Study on Reliance Industries Limited (RIL) - Dr. Ramprakash O. Panchariya (International Journal of Engineering and Management Research, 2021)
Purpose: The present research aims to study Corporate Social Responsibility (CSR) expenditure of Reliance Industries Limited (RIL). Design / methodology / approach: The study is based on secondary data collected for Reliance Industries Limited for FY 2015-16 to 2019-20 from national CSR data portal, Ministry of Corporate Affairs, Government of India for the research work. Statistical measure like one sample T-Test and Pearsons Correlation has been used for analyzing the data. Findings: The study reveals that there has been a significant increase of Rs. 350.93 crore in actual CSR spent of RIL i.e. increase of 62.92% in FY 2019-20 over FY 2015-16. From the study it is also found that RILs Actual CSR Spending is more as compared to CSR Prescribed during FY 2016-17 to 2019-20 whereas it is same in FY 2015-16 and the CSR Ratio of RIL is as per the SEBIs regulation of 2% during FY 2015-16 to 2019-20.